Artefak Bahasa dalam Pemilihan Kepala Daerah (Pilkada) - Siti Masitoh (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2013)
Indonesia is rich of cultural heritage since it consists of more or less 34 provinces and every one ofwhich has its own characteristics which is different from others. It is a matter of fact that local colorprovides very valuable local wisdom which will determine the character building. Thus, theunderstanding of our own culture is really important to be wiser citizens. This article discusses aboutthe recent cultural phenomena in district election in which its candidates think that the use of languageartifact is applicable now days. This phenomena is also possible to happen in other places and itsupports the discussion of culture to be more fruitful.